Neuroprotective and Anti-Apoptotic Activity of Anthranilamide Pyrazolo[1,5-a] Pyrimidine Derivative against Parkinson’s Disease Model in Rotenone-Induced SH-SY5Y Cells - Yerramsetty, Suresh; Ayyagari, Lavanya; Kanth Makani, Venkata Krishna; Mendonza, Jolly Janette; Ajjarapu, Suchitra Maheswari; Kamal, Ahmed; Pawar, Smita C.; Bhadra, Manika Pal (International Journal of Pharmaceutical Investigation, 2025)
Parkinson’s Disease (PD) is the second most prevalent form of neurodegenerative disorder distinguished by progressive and specific loss of dopaminergic neurons in the Substantia Nigra (SNPc) resulting in abnormal movement and bradykinesia including multiple behavioral complications. Despite having diverse therapeutic approaches, noticeable reversals of the pathophysiological and behavioral features are yet to be observed. Here we report one of the Anthranilamide Pyrazolo[1,5-a] pyrimidine (known CDK inhibitors) derivate, C2 that has shown a neuroprotective effect in PD models of SH-SY5Y cells (neuroblastoma origin). This is one of the first studies that show C2 can act as a potent CDK1 inhibitor and additionally decipher its neuroprotective activity in Parkinson’s disease. C2 neutralizes the rotenone-induced overexpression of pro-apoptotic caspases including caspases 9 and 3 and Bax. C2 showed neuroprotective activity and regulates neuronal cell death via modulation of p38/JNK MAPK family protein expression that are often dysregulated upon rotenone treatment. Collectively, these results implicate the role of C2 as a potential neuroprotective compound to treat PD pathogenesis. Aim To investigate the neuroprotective and anti-apoptotic effects of an anthranilamide pyrazolo[1,5-a] pyrimidine derivative(C2) in a Parkinson’s Disease (PD) model using rotenone-induced SH-SY5Y cells. Background Although there are several therapeutic approaches, such as levodopa and carbidopa, that alleviate the transient symptoms of Parkinsonism, an effective drug candidate capable of decelerating disease progression and preventing neuronal apoptotic death has yet to be identified. Materials and Methods To address this, we have used the rotenone-induced SH-SY5Y PD model to evaluate the protective role of C2 through functional assays. Results We observed that C2 treatment reduces ROS production and provides protection to SH-SY5Y cells against apoptosis. C2 pretreatment improved cell viability and reduced apoptosis in SH-SY5Y cells exposed to rotenone, demonstrating its protective effects. C2 neutralizes the rotenone-induced overexpression of pro-apoptotic caspases including caspases 9 and 3 and Bax. C2 showed neuroprotective activity and regulates neuronal cell death via modulation of p38/JNK MAPK family protein expression that are often dysregulated upon rotenone treatment. Docking analyses showed that C2 binds to the ATP binding pocket of CDK1 with spontaneity comparable to other inhibitors, as indicated by ΔG values. C2 also interacts with the molecular fork like other inhibitors, suggesting it may be a potent CDK1 inhibitor, similar to Roscovitine. Conclusion Our present study highlights that C2 has neuroprotective effects in the SH-SY5Y rotenone-induced PD model. Computational docking analyses revealed that C2 binds to the ATP pocket of CDK1 similarly to known inhibitors like Roscovitine, that shows neuroprotective properties. C2 reduces pro-apoptotic caspases (caspases-9 and -3) and Bax levels. Further, C2 also regulates p38/ JNK MAPK protein expression, which is often dysregulated by rotenone. Collectively, these results implicate the role of C2 as a potential neuroprotective compound to treat PD pathogenesis.
Keywords: PD (Parkinson’s Disease); Pyrazolo[1,5-a] pyrimidine derivatives; Rotenone; Dopaminergic neuron; CDK1; Molecular docking